Prosocial and externalizing behaviors in children raised by different-and same-gender parent families: new directions in parenting research - Baiocco, Roberto; Favini, Ainzara; Pistella, Jessica; Carone, Nicola; Speranza, Anna Maria; Lingiardi, Vittorio (Frontiers in Psychology, 2024)
Introduction Limited research focused on the association between parenting practices and children’s prosocial and externalizing behaviors comparing same- and different-gender parent families. The present study considered 76 Italian families (73% same-gender and 27% different-gender parent families) with 8-year-old (SD = 2.17; 49% assigned female at birth) children born through assisted reproductive techniques, to explore parenting practices and children’s prosocial and externalizing behaviors. Method We ran a Multiple-group-by-couple Structural Equation Model in which we estimated the predictive role of parenting on children’s behaviors, controlling for age, gender, and family socioeconomic status using the Maximum Likelihood estimation. Results Results showed that both same- and different-gender parent families reported high levels of parental warmth and very low levels of hostility and rejection; regarding children’s behaviors, both same- and different-gender parent families reported high levels of prosociality and low levels of externalizing behaviors. In addition, same-gender parents reported significantly higher levels of children’s prosociality and parental warmth than different-gender parents. Regarding associations between parenting practices and behaviors, we found a positive association between positive parenting practices and increasing children’s prosocial behaviors and decreasing children’s externalizing behaviors, in both same- and different-gender families, controlling for family background characteristics. Conclusion The present study encourages future research to investigate how specific parenting practices can influence behavioral adjustment in children, focusing on same-gender parent families.